Overview of High Throughput Sequencing Technologies to Elucidate Molecular Pathways in Cardiovascular Diseases - Churko, Jared M. (2013)
High throughput sequencing technologies have become essential in studies on genomics, epigenomics, and transcriptomics. While sequencing information has traditionally been elucidated using a low throughput technique called Sanger sequencing, high throughput sequencing (HTS) technologies are capable of sequencing multiple DNA molecules in parallel, enabling hundreds of millions of DNA molecules to be sequenced at a time. This advantage allows HTS to be used to create large data sets, generating more comprehensive insights into the cellular genomic and transcriptomic signatures of various diseases and developmental stages. Within HTS technologies, whole exome sequencing can be used to identify novel variants and other mutations that may underlie many genetic cardiac disorders, whereas RNA sequencing (RNA-seq) can be used to analyze how the transcriptome changes. Chromatin immunoprecipitation sequencing (ChIP-seq) and methylation sequencing (Methyl-seq) can be used to identify epigenetic changes whereas ribosome sequencing (Ribo-seq) can be used to determine which mRNA transcripts are actively being translated. In this review, we will outline the differences in various sequencing modalities and examine the main sequencing platforms on the market in terms of their relative read depths, speeds, and costs. Lastly, we will discuss the development of future sequencing platforms and how these new technologies may improve upon current sequencing platforms. Ultimately, these sequencing technologies will be instrumental in further delineating how the cardiovascular system develops and how perturbations in DNA and RNA can lead to cardiovascular disease.